Agricultural landscapes, ecosystem services and regional competitiveness—Assessing drivers and mechanisms in nine European case study areas. (July 2018) - Schaller, Lena; Targetti, Stefano; Villanueva, Anastasio J.; Zasada, Ingo; Kantelhardt, Jochen; Arriaza, Manuel; Bal, Tufan; Fedrigotti, Valérie Bossi; Giray, F. Handan; Häfner, Kati; Majewski, Edward; Malak-Rawlikowska, Agata; et al.
Abstract: Agricultural landscapes affect regional development and competitiveness in a way far beyond the production of agricultural commodities. However, comprehensive assessments of the relevant cause-effects between agricultural landscape and regional competitiveness are complex and they require a range of ecological, economic and social aspects to be considered. This study proposes an stakeholder-based 'Analytic Network Process' applied in nine European case-study areas in order to assess the role of economic actors, ecosystem services, socio-economic benefits and regional competitiveness in the agricultural landscape system. The results reveal that agricultural food production is still perceived as a major element for creating value from landscapes. However in some case studies, the importance of non-marketable, socio-cultural and environmental public good-type ecosystem services outweighs the importance of agricultural production. Region-specific variations of cause-effect relationships are discussed and a range of drivers, related to biophysical conditions, land-use patterns, agricultural management and remoteness are identified. Our study reveals the perception of non-monetary services and their impact on regional competitiveness and provides considerations on entry points for rural policies promoting landscape valorisation.